Migrantes en el estado de México: patrones migratorios diversos y formas de organización - Felipe González Ortiz (Ciencia Ergo Sum)
After some reflections about mexiquenses in the United States and their specific migratory phenomena, it is possible to detect three types of migrants: non-indigenous migrants, socialized in rural environments; non-indigenous migrants, socialized in urban environments; indigenous migrants, socialized in urban environments. This characterization allows us to establish a distinction in the specific forms of social organization and distinguish different migratory patterns. This work represents a first sight of the phenomena and a first systematic approach to international migration of population from the State of Mexico